Cities are good for you : the genius of the metropolis - Leo Hollis (New York : Bloomsbury Press, 2013)
At the beginning of the century, we became 50% urban as a global population, and by 2050 we're going to be up to 70% urban. Cities could either be our coffin or our ark. Hollis presents evidence that cities can deliver a better life, and investigates how cities all over the world are tackling climate change, population growth, poverty, shifting work patterns and the maintenance of the fragile trust of their citizens.